Pengaruh Social Media Marketing, Brand Awareness, Brand Image Dan Brand Trust Terhadap Loyalitas Pelanggan Ultras Malang - Ahmad Hikam; Rois Arifin; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2022)
Abstractrelationship between on customer loyalty Ultras Malang. This research uses a study method on Ultras Malang customers where data is obtained by distributing questionnaires to Ultras Malang customers in Malang city which are selected by purposive sampling. Determination of the number of samples using the Maholtra formula and the results obtained were 105 respondents. The analytical method used in this research is instrument test (validity test, reliability), normality test, classical assumption test (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (F test and t test), processing the coefficient of determination test. data using SPSS 23. The results of this study indicate that Social Media Marketing, brand awareness, brand image and brand trust simultaneously affect customer loyalty partially Social Media Marketing affects customer loyalty, brand awareness partially affects customer loyalty, brand image partially partial effect on customer loyalty customer loyalty, brand trust partially does not affect customer loyalty.Keywords : social media marketing, brand awareness, brand image, brand trust